A web-based controlled greenhouse system and monitoring the system's data - (:unkn) unknown (My University, 2011)
In this study, the control of a greenhouse system and monitoring the system data over the internet is intended. Depending on temperature and humidity, a system controlling this greenhouse is designed. The measured values received from the system are stored in a database and then these values can be monitoring through a database communication protocol through a web interface. Apache web server for the web infrastructure for the system is preferred. Remote users can observe the data belonging to the greenhouse system using PHP based web pages via the internet at any time, or may adjust the parameters for the physical configuration of the greenhouse. In this way, users from anywhere and at any time can check and track automation data without any obligation of being existence. In addition, the recorded measured values and the changes depending on the time in the system's database would shed light on the approaching studies about estimated curves. Moreover, data mining technics would be considered in future studies to develop more efficient methods of finding convenient values of the greenhouse's setting configuration, regarding this paper. Therefore the methods could be used to increase the efficiency and the quality of the greenhouse management system. © 2011 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Apache web server; Data monitoring; Greenhouse automation; PIC 16F877; Remote control; Web based control